(untitled) (Indian Journal of Arid Horticulture, 2017)
Eight date palm cultivars i.e. Khadrawy, Shamran, Zahidi, Braim, Chipchap, Sabiah, Seddami and Medjool commonly grown in Bikaner were studied for their morphological and physiochemical characters at ICAR-CIAH, Bikaner, Rajasthan, India during the year 2015-16. The results revealed that differences in vegetative characters were statistically significant except in the length of leaves. The fruit colour, size, weight, stone size and grooves in stone are useful characters for identification of date palm cultivars and the maximum plant height (5.34 m) and length of pinnae (44.79 cm) was recorded in cv. Seddarni whereas, minimum height (2.16 m) and length of pinnae (33.64 cm) in cv. Khadrawy. Breadth of pinnae range from 1.96 cm in cv. Shamran to 2.85 cm in Medjool. Maximum leave length (3.25 m) was recorded in cv. Braim whereas, minimum in cv. Medjool (2.40 m). Among the varieties maximum fruit size i.e. length (4.41 cm), dia (2.92 cm), fruit weight (21.49 g), stone weight (1.97 g) and pulp: stone ration (12.93) was produced by cv. Medjool and minimum fruit size i.e. fruit length (2.91 cm), diameter (1.93 cm), fruit weight (7.62 g) and stone weight (1.09 g) in cv. Sabiah . The total soluble solid (36.55 % ), total sugars (36.35% ), reducing sugar (31.54%) was recorded maximum in Braim whereas, minimum total soluble solid (32.83 %) and reducing sugar (27.72%) in a Sabiah, total sugars (31.39%) in cv Shamran. Non reducing sugars were maximum (5.50%) in a Seddami and minimum in cv. Shamran (2.70%). Maximum acidity content was recorded (0.31 %) in Sabiah and minimum (0.21 %) in Braim, maximum ascorbic acid was recorded in Medjool (7.83 mg/lO0g pulp) and minimum in Shamran (4.65 mg/100 g).